Tableau calculi for description logics revision - Moguillansky, Martín O. (2007)
Focusing on the Ontology Change problem, we consider an environment where Description Logics (DLs) are the logical formalization to express knowledge bases, and the integration of distributed ontologies is developed under new extensions and modifications of the Belief Revision theories yielded originally in [2]. When using tableaux algorithms to reason about DLs, new information is yielded from the models considered in order to achieve knowledge satisfiability. Here a whole new theory have to be reinforced in order to adapt belief revision definitions and postulates to properly react over beliefs on extensions generated from these DL’s reasoning services. In this text we give a brief background of these formalisms and comment the research lines to be taken in our way to this goal.